Implementasi Zakat Profesi terhadap Aparatur Sipil Negara di Pemerintah Daerah Kabupaten Bone Bolango - Faisal Pakaya; Lahaji Lahaji (Al-Mizan (e-Journal), 2019)
This study aims to discuss the implementation of professional zakat in the State Civil Apparatus in Gorontalo District Government. This research is a field research with data collection methods such as observation, interviews, questionnaires and documentation. The data collected is processed and analyzed with descriptive qualitative. The results showed that: First, the Regional Government of Bone Bolango District had carried out the mandate of Law Number 23 of 2011 and Government Regulation Number 14 of 2014; Second, the State Civil Apparatus in the Regional Government of Bone Bolango Regency has a different understanding related to the existence of professional zakat; and Third, the receipt of professional zakat in the Regional Government of Bone Bolango Regency is quite high and this can improve the welfare of the community if it is distributed according to the procedure.